The Introduction of Predatory Bird Lanius Schach from Yogyakarta to Salibabu Island for Controlling Sexava Spp. On Coconut Palm - F X WAGIMAN; NUGROHO SUSETYO PUTRO; FREDY LALA; MELDY L. A. HOSANG (Buletin Palma, 2014)
The chronic, endemic, and outbreak of a longhorn grasshopper (Sexava spp.) occurs at central production of coconut palms in Indonesia, such as North Sulawesi, Maluku, North Maluku, Papua and West Papua. Farmers suffer from very significant economic-losses due to the pest attack, for example in Salibabu Island. Previous study in 2010 at District of Bolaang Mongondow Selatan, Province of North Sulawesi, revealed that the predatory bird Lanius schach is promising for biological control of the pest. In areas of the pest outbreak, the bird is absent, on the other hand, it is abundant in Yogyakarta. As many as 30 males and 10 females of the bird were introduced to Salibabu Island and they were intended to control the pest. All birds were successfully introduced and released at Sub District of Moronge. Within 2 months after release the birds were observed at 5 km away from the release site. Trends on reduction of the pest population-density and leaf damage were observed within 2 months after predator release. Next program on acceleration of the predator increase in numbers is urgently attempted to keep the predator being under controlled within expected period of 3 years. ABSTRAKIntroduksi Burung Predator Lanius schach dari Yogyakarta ke Pulau Salibabu untuk Pengendalian Sexava Spp. pada Tanaman Kelapa Ledakan populasi belalang antena panjang (Sexava spp.) yang kronis dan endemik terjadi pada sentra produksi kelapa di Indonesia, seperti Sulawesi Utara, Maluku, Maluku Utara, Papua dan Papua Barat. Serangan hama ini mengakitkan petani mengalami kerugian ekonomi yang sangat signifikan, misalnya serangan di Pulau Salibabu. Penelitian awal pada tahun 2010 di Kabupaten Bolaang Mongondow Selatan, Provinsi Sulawesi Utara, mengungkapkan bahwa predator burung Lanius schach berpeluang sebagai agens pengendalian hayati hama tersebut. Di daerah ledakan populasi hama, burung ini tidak ada, tetapi, burung tersebut berlimpah di Yogyakarta. Sebanyak 30 jantan dan 10 betina burung berhasil dintroduksi ke Pulau Salibabu. untuk mengendalikan hama tersebut, predator burung Lanius schach telah diintroduksi sebanyak 30 ekor jantan dan 30 ekor betina ke Pulau Salibabu. Predator yang berhasil diintroduksi ini dilepas di Kecamatan Moronge. Dua bulan setelah pelepasan, burung dapat diamati pada jarak 5 km dari lokasi pelepasan. Kepadatan populasi hama dan kerusakan daun cenderung menurun dalam waktu 2 bulan setelah pelepasan predator. Program berikutnya adalah percepatan peningkatan jumlah predator dan diusahakan supaya predator dapat diawasi dalam jangka waktu sekitar 3 tahun. Kata kunci: Introduksi, tanaman kelapa, Sexava, Lanius schach, pengendalian hayati.